Sprachgebrauch und Spracheinstellungen in der Deutschschweiz. Pfarrpersonen als sprachbewusste Sprecherinnen und Sprecher im Fokus - Oberholzer, Susanne (Linguistik Online, 2017)
The relation between Swiss German dialects and Standard German has been subject to public and scholarly debates for over 100 years. Among the most frequently discussed points are the appropriateness of spoken Standard German in different contexts and the attitudes of Swiss people towards the two varieties. This paper summarises the results of a completed research project (Oberholzer in Vorb.), which surveyed language use and language attitudes in Swit-zerland for a specific group of speakers: pastors and priests working in German-speaking Switzerland. The paper shows how pastors and priests make use of the diglossic situation and the possibility to code-switch in Sunday services. The use of Standard German emerges as an important communicative resource in German-speaking Switzerland. In addition, real language use and intended language use match to a high degree; this shows the degree of language awareness of this particular group in a diglossic situation. Furthermore, a relatively new approach – the assumption that several mental models of High German coexist – helps to show differentiated language attitudes and to contradict some of the most common stereotypes regarding Standard German in German-speaking Switzerland. The attitudes towards Standard German in this study are significantly more positive than those observed in previous studies.